The Impact of Inclusive Education on the Social and Emotional Development of Children - Zohidjonovna, Ruziyeva Nigora (International Journal on Integrated Education, 2026)
Inclusive education, which integrates students of all abilities into the same classrooms, is becoming an educational priority in Uzbekistan as well. Beyond academic gains, inclusive settings are hypothesized to foster students’ social and emotional development by promoting empathy, self-esteem, and positive peer relationships. This study examines how inclusive classrooms impact children’s social-emotional skills and well-being compared to segregated settings. This study aims to investigate the impact of inclusive classrooms on children’s social-emotional skills and overall well-being in comparison to traditional segregated educational settings. Utilizing a mixed-methods design, data were collected from students, teachers, and parents in multiple schools across Tashkent. Quantitative measures assessed social-emotional abilities, empathy, peer acceptance, self-concept, and psychological well-being, while qualitative interviews and focus groups provided deeper insights into lived experiences and perceptions regarding inclusion. Findings reveal that inclusive classrooms create a supportive and empathetic learning environment where students demonstrate higher levels of social competence, stronger peer bonds, and improved emotional regulation. The study also highlights the critical role of teachers and parents in facilitating these positive outcomes through targeted support and collaboration. These results underscore the value of inclusive education not only as a means of upholding the rights of students with disabilities but also as a strategy to enhance social and emotional development for all learners